Searching for Germane Questions in the Ethnobiology of Food Scouting. Issue Volume 43:Issues 1(2023) (March 2023) - Zocchi, Dauro M.; Mattalia, Giulia; Aziz, Muhammad Abdul; Kalle, Raivo; Fontefrancesco, Michele F.; Sõukand, Renata; Pieroni, Andrea
In the past two decades, ethnobiologists have increasingly paid attention to the scouting and documentation of endangered corpora of local food elements and associated traditional knowledge. In this endeavor, food scouting encompasses the methodological tools used for mapping, inventorying, and documenting food and food-related resources. The growing body of research in this field is shedding light on the potentialities of these practices in obtaining baseline data regarding food heritage, which can, in turn, empower local communities in their dynamic understanding and safeguarding of this resource. While food scouting have been gaining an important role in current food and gastronomic ethnobiological research, as well as in other fields of study (e.g., geography and anthropology), little attention has been paid thus far to the methods and approaches underpinning these activities. To partially fill this gap, this contribution aims to tackle some methodological issues connected to the documentation of food and gastronomic elements embedded in local knowledge. Acknowledging the plethora of methods applicable in food scouting research, we describe three specific applications of food scouting to elicit data on local food diversity, highlighting their prospects and limitations. The first case addresses market surveys to obtain baseline data on the local food systems and their associated diversity, the second focuses on context-based freelisting methods for eliciting wild food plant uses, and the third discusses methods for scouting and inventorying artisanal food products. Acknowledging the contributions of Justin Nolan to the advancement of methods in the field of ethnobiology, we suggest that the methodological toolkit of food scouting should include ad hoc transdisciplinary platforms codesigned together with local food actors.